PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM MELALUI PENDEKATAN REKONTRUKSI SOSIAL - Nia Juwita Purnika Nia sari; Dwi Wulan Sari; Kiki Ayu Hermawati (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Changes in curriculum development are always undergoing improvements and updates in line with the times. As a basis for actualizing education, the curriculum does not only focus on knowledge and skills but other important aspects such as interactions between individuals and the social environment. This study aims to analyze the development of the Islamic religious education curriculum through a social reconstruction approach. The method used is qualitative with the type of library research. The results of the study show that social reconstruction as an approach in the Islamic religious education curriculum has the view that humans always need interaction in solving problems in their lives. Thus, the role of the social reconstruction approach in curriculum development is urgently needed to deal with the problems faced by society. Education will be directed to be cooperative, collaborative, and closer to their environment, to be able to prepare potential students and be ready to accept all changes that occur in the future.